(3eTGQb GdCfhGQ Ydi UMGM GdBKGQs - (3YjGV Hf ehSi Hf YjGV Hf YeQhf GdjMUHj GdSHJj, CHh GdaVd,J (B544 (3g` s ((3CMeO Hf jhSa GdYWGQ s)
(3ChdgG (B:s
(3GdMeO ddg eXgQ Ojfg GdeHjf HYK eMeOkG Ydjg GdSdGe Edi cGaI Ndbg HcJGHg hHjf Ydi dSGf fHjg ef efGgLI hTQYJg eG hcd fai GdJMQja Yfg s
(3BNQgG (B:s
(3hjMJed Cf JeGeg (B: (3cgGJjf , Ch gcPG hVe CUGHYg , ceG bGd ai GdMOjK GdBNQ (B: (3cgGJjf haQb CUGHYg cedJ GdCHhGH GdKdGK hHceGdg ced LejY GdOjhGf s
(3jdjgG ai hQbI (B223 (3bUjOI dYjGV fSNgG hbGHdgG QVhGf Hf YHO Gddg GdLfOi SfI (B949 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B16s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1687s
Keywords: (3GdMOjK h GdeUWdMs